Selection of Alternative Domestic Wastewater Treatment Technology with Using Life Cycle Assessment (LCA) Approach: Case Study Settlement Area of Riverbank Karang Mumus of Samarinda City, East Kalimantan - Rininta Triananda Noor; Prayatni Soewondo (Universitas Trisakti, 2018)
Aims: This study aims to analyze and select wastewater treatment technology that can be applied to riverbank settlement areas through environmental impact evaluation using LCA. The technology option is selected through the physical condition of the settlement environment on the river banks and then analyzed descriptively by making a flow chart of the processing technology options and compared with the wastewater treatment technologies that have been applied to residential areas of river banks or other swamp settlements. Methodology and results: The technology options will be analyzed and evaluated for potential environmental impacts of the construction and operation phase, using LCA through SimaPro8.4 software with an impact analysis using CML2 Baseline 2000. The impacts analyzed include acidification, eutrophication, global warming, ozone depletion. The results showed that the selected technological options were septic tanks, tripikon-s, and biofilter. In an environmental impact analysis it is known that the construction phase is a phase that contributes greatly to the potential environmental impacts. The potential for acidification and global warming are the dominant potential impact from the three technology options, with a contribution of 2.01x10-10 kgSO2-eq for the potential of acidification and 1.11x10-10 kgCO2-eq for global warming potential with biofiltration as a main contributor. The eutrophication potential is caused by nutrients (Total Nitrogen and Phosphorus) that come out along with the treated wastewater at the operating stage. The greatest eutrophication potential is generated on the Tripikon-S, at 2.3x10-10 kgPO4-eq. The potential for ozone depletion, biofiltration contributes significantly to 3.09x10-12 kgCFC-11-eq. Conclusion, significance and impact study: Based on the comparison of technology, it is known that Tripikon S has the potential for environmental impact is quite minimal and can be an option to be applied to the river banks.